Challenging the phylogenetic relationships among Echinococcus multilocularis isolates from main endemic areas - Lallemand, Séverine (2024)
Alveolar echinococcosis (AE) is a rare but severe disease that affects more than 18,000 people worldwide per year. The complete sequencing of the mitochondrial genome of Echinococcus multilocularis has made it possible to study the genetic diversity of the parasite and its spatial and temporal evolution. We amplified the whole mitochondrial genome by PCR, using one uniplex and two multiplex reactions to cover the 13,738 bp of the mitogenome, and then sequenced the amplicons with Illumina technology. In total, 113 samples from Europe, Asia, the Arctic and North America were analyzed. Three major haplogroups were found: HG1, which clustered samples from Alaska (including Saint-Lawrence Island), Yakutia (Russia) and Svalbard; HG2, with samples from Asia, North America and Europe; and HG3, subdivided into three micro-haplogroups. HG3a included samples from North America and Europe, whereas HG3b and HG3c only include samples from Europe. In France, HG3a included samples from patients more recently diagnosed in a region outside the historical endemic area. A fourth putative haplogroup, HG4, was represented by only one isolate from Olkhon Island (Russia). The increased discriminatory power of the complete sequencing of the E. multilocularis mitogenome has made it possible to highlight four distinct geographical clusters, one being divided into three micro-haplogroups in France.